PERANCANGAN BUSANA BERKELANJUTAN BAGI MARKET URBAN SEBAGAI UPAYA REVITALISASI TENUN SUMBA TIMUR - Sri Ningsih, Yosepin; Fiona Nathania Elfrida (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2023)
The local product of the Sumba region, namely woven cloth, is widely known to the public thanks to various efforts done by various agencies. However, from the various existing weaves, only ikat weaving that is wellknown for the wider community, while there is another woven, namely Lau Pahikung, which is also a specialty of the region. This research presents revitalization process of Lau Pahikung weaving through fashion design products aimed for urban communities. The research process uses a qualitative research approach with the ATUMICS and Trend Forecasting methods that being done in sustainable way. The product uses the main material of Lau Pahikung weaving which is processed in ecofriendly way so that the selection of material combinations also considered sustainable materials, namely denim material from the Badjatex label which already has an environmentally friendly fabric production certificate. The process resulting ready-to-wear fashion collection titled Denim Revolution, a collection which inspired from the basic form of Sumbanese traditional cloth using Lau Pahikung and other sustainable material for the preservation of Lau Pahikung woven. Keywords: ATUMICS, fashion, Lau Pahikung, Sumba, sustainability